Generalized Degenerative Joint Disease in Osteoprotegerin (Opg) Null Mutant Mice. (September 2015) - Bolon, B.; Grisanti, M.; Villasenor, K.; Morony, S.; Feige, U.; Simonet, W. S.
Bone structure is modulated by the interaction between receptor activator of nuclear factor–κB (RANK) and RANK ligand (RANKL). Osteoprotegerin (OPG), a decoy receptor for RANKL, modifies osteoclast-mediated bone resorption directly and spares articular cartilage indirectly in rodents with immune-mediated arthritis by preventing subchondral bone destruction. The OPG/RANKL balance also seems to be critical in maintaining joint integrity in osteoarthritis, a condition featuring articular bone and cartilage damage in the absence of profound inflammation. The current study explored the role of OPG in sparing articular cartilage by evaluating joint lesions in adult C57BL/6J mice lacking osteoprotegerin ( Opg − /− ). At 3, 5, 7, 9, and 12 months of age, both sexes of Opg − /− mice developed severe degenerative joint disease (DJD) characterized by progressive loss of cartilage matrix and eventually articular cartilage. Lesions developed earlier and more severely in Opg − /− mice relative to age-matched, wild-type ( Opg + /+ ), or heterozygous ( Opg + /− ) littermates ( P ≤ .05). The femorotibial joint was affected bilaterally at 3 months, while other key weight-bearing diarthrodial joints (eg, coxofemoral, scapulohumeral, humeroradioulnar) were affected later and unilaterally. Cortical bone in subchondral plates and long bone diaphyses of Opg − /− mice but not Opg +/+ or Opg + /− animals was osteoporotic by 3 months of age ( P ≤ .05); the extent of porosity was less than the degree of DJD. Closure of the physes in long bones ( P ≤ .05) and cartilage retention in the femoral primary spongiosa ( P ≤ .05) affected chiefly Opg − /− mice. These data suggest that OPG plays an essential direct role in maintaining cartilage integrity in the articular surfaces and physes.